Product-portfolio management: A framework based on Methods, Organization, and Strategy - Jugend, Daniel [UNESP]; Silva, Sergio Luis da (Sage Publications Ltd, 2014)
Product-portfolio management is a decisive element for the good performance of new product development and compliance with business objectives because it not only defines new product projects but also defines revisions, updates, and even decisions regarding the discontinuation of products that are produced and commercialized. Decision-making evaluations related to the portfolio are considered one of the main critical factors for success associated with new product development, and these decisions' primary characteristics are the high number of project ideas with great uncertainty about results, making the management complex. This article proposes a framework with the specific objective of presenting an approach that could be useful to product-portfolio management. The framework proposed in this article presents a holistic perspective of product-portfolio management, suggesting the use of a set of formal management methods for not only evaluating product projects but also extending to organizational aspects and including them in strategic planning and portfolio reviews.
Keywords: New product development; product-portfolio management; framework